Breakfast skipping and its association with adolescent bullying victimization: a large-scale multicenter cross-sectional study - Juan Du; Yufeng Liang; Fanfan Xu; Xiayun Zuo; Qiguo Lian (BMC Public Health)
Abstract Background This study aims to estimate the prevalence of breakfast skipping among Chinese adolescents and to investigate the association between breakfast skipping and multiple forms of bullying victimization. Methods We used 2020/2021 data from the Database for Youth Health program in Shandong, China, and included 24,041 students in grades 7–12 in the analysis. Breakfast skipping was defined as the self-reported omission of breakfast daily in the past 7 days. We compared the prevalence of breakfast skipping between bullied and non-bullied students, then estimated the adjusted odds ratios (AORs) and 95% confidence intervals (CIs) for the association between breakfast skipping and multiple forms of bullying victimization after adjusting for potential covariates. Results About one in ten students (9.80%) reported skipping breakfast daily, the prevalence was higher in traditional (19.59% vs. 8.36%) and cyber (19.67% vs. 8.51%) bullied students than non-bullied students. Bullying victimization presented greater likelihood of breakfast skipping (traditional: AOR (95% CI), 1.91(1.17–2.06); cyber: 1.87(1.70–2.07); any: 2.16(1.99–2.34)). We also observed a relationship between breakfast skipping and victimization type. Traditional only (AOR (95% CI):2.23(1.96–2.54)), cyber only (AOR (95% CI):2.25(1.98–2.56)), and both (AOR (95% CI):2.03(1.82–2.26)) victimization were all positively associated with breakfast skipping. Conclusion Among Chinese adolescents, breakfast skipping is prevalent and consistently linked to both traditional and cyber bullying victimization.